THE HISTORY OF THOUGHT: PHILOSOPHY IN THE VIEW OF MUSLIM PHILOSOPHERS OF THE MIDDLE AGES - Febta Pratama (Universitas Negeri Yogyakarta, 2018)
ABSTRACK This research tries to see how the development of Muslim scholarship and travel, especially in the field of philosophy. Describes how the philosophers studied then develop and spread the knowledge gained. The method used is the method of history that consists of four phases i.e. heuristics, critique, interpretation, and historiography. The results showed that there was already a Muslim scholarly tradition since the time of the prophetic. The entry of Muslim civilization to the philosophy starts when the emergence of scientific groups such as the Al Khawarijh, Muta'zillah, and Ahl Sunnah Wal Jammaah. The tradition of science especially philosophy started by a civilization of Islam since the fall of Byzantium and rebuilding of Bait Al Hikmah as a place to translate books from Greece. Then the Muslim tradition of scientific philosophy continued by Muslim figures and also philosophers such as Ibn Sina, Ibn Rushd, Al Farabi. It is these philosophers who developed a philosophy of science especially become the reference of Western philosophers in afterwards.Keyword. Philosophy, Philosophers, Muslim